2021
DOI: 10.1186/s12939-021-01452-z
|View full text |Cite
|
Sign up to set email alerts
|

Equity in newborn care, evidence from national surveys in low- and middle-income countries

Abstract: Background High coverage of care is essential to improving newborn survival; however, gaps exist in access to timely and appropriate newborn care between and within countries. In high mortality burden settings, health inequities due to social and economic factors may also impact on newborn outcomes. This study aimed to examine equity in co-coverage of newborn care interventions in low- and low middle-income countries in sub-Saharan Africa and South Asia. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
2
5
0
Order By: Relevance
“…Conversely, there were far fewer inequities by maternal age, largely indicating that adolescent and other young mothers do not receive less or poorer-quality care for their newborns as compared to older mothers. This aligns with the findings from a study of 16 low- and middle-income countries found that maternal age was a significant predictor of newborn care only in Senegal and was non-significant in all other countries [ 24 ]. However, we found several disparities between the youngest and oldest maternal age groups in the private for-profit sector.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Conversely, there were far fewer inequities by maternal age, largely indicating that adolescent and other young mothers do not receive less or poorer-quality care for their newborns as compared to older mothers. This aligns with the findings from a study of 16 low- and middle-income countries found that maternal age was a significant predictor of newborn care only in Senegal and was non-significant in all other countries [ 24 ]. However, we found several disparities between the youngest and oldest maternal age groups in the private for-profit sector.…”
Section: Discussionsupporting
confidence: 90%
“…Neonates from the poorest households were less likely to be born in a facility and were far less likely to receive care outside the home if they experienced fever. Among neonates born at home with a skilled attendant, those from the poorest households were less likely than those from the wealthiest to receive essential newborn and postnatal care, which aligns with findings from a 2021 study on co-coverage and equity of newborn care [ 24 ]. Socioeconomic disparities were largest among neonates born at home with a SBA and smallest among neonates born in the public sector.…”
Section: Discussionsupporting
confidence: 78%
“…Areas with high RDS-associated neonatal mortality are also concentrated in regions characterized by the highest rates of social vulnerability and lower socioeconomic status, with younger mothers, lower maternal schooling, and lower prenatal care visits [ 17 , 45 ]. All these factors are probably associated with higher neonatal mortality rates due to factors that include a poorer access to appropriate newborn care interventions [ 46 ] and to RDS good practices management strategies, contributing to RDS-associated neonatal deaths [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“… 11 Co-coverage can more specifically show the proportion of the population receiving most or all of the recommended postnatal care interventions, providing a more granular understanding of gaps in care provision to better inform service development needs. 51 Furthermore, co-coverage can be useful for equity analyses to identify high-risk groups lagging behind 25 , 51 54 and may be particularly advantageous when used to replace multiple coverage estimates in multicountry or time trend analyses. 16 , 51 , 55 However, country-specific questionnaire adaptations or differences may inhibit cross-country comparison.…”
Section: Discussionmentioning
confidence: 99%